The Pendampingan Inklusi Finansial Melalui Aplikasi Sikapi Uangmu pada UMKM Eks-PMI Kabar Bumi Ponorogo - Novita Erliana Sari; Maretha Berlianantiya; Aprilia Syafitri; Aji Nur Abdurrohman; Reza Krisyulinda (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The understanding of MSME actors who are former migrant workers who are members of the "KABAR BUMI PONOROGO" organization regarding the availability of access to various institutions, formal financial products, and services or what is usually called financial inclusion is still very low. In general, they have difficulty understanding financial inclusion well, so they cannot access the use of financial products and services in the form of loans, insurance, savings, mobile banking, electronic money, or various capital that can be accessed at any time. This lack of knowledge means that their businesses are often hampered because they use conventional systems. The Financial Services Authority (OJK) has also issued an Android-based application that provides a complete review of financial inclusion. Unfortunately, this application has not been able to reach MSME owners who are former migrant workers in Ponorogo. Based on this problem, the community service team provided financial inclusion assistance through the Ilmu Uangmu application to ex-PMI KABAR BUMI PONOROGO MSMEs. This activity aims to build business owners' insight into financial inclusion, so they can expand their businesses globally. The activity was carried out for two days, starting with giving participants a pretest to do, providing training by accessing the "Sikapi Uangmu" application using the Android they have, giving participants the opportunity to make presentations, giving quizzes, conducting simple financial recording training, finally ends with a post test. The post test results showed significant changes in the participants' scores. This shows that this activity was successful by increasing participants' awareness and understanding regarding financial inclusion.